IMPLEMENTASI METODE LEAN SIX SIGMA GUNA MENGELIMINASI DEFECT PADA PROSES PRODUKSI PURIFIED GYPSUM DI PT. AAA - Romadhani, Febri; Mahbubah, Nina; Kurniawan, M Dian (Universitas Bina Taruna Gorontalo, 2021)
PT. AAA is a chemical-based producer with zero defect program in term of maintaining product quality. However, there were found waste which were higher than based line quality acceptance through production process line of purified gypsum. This research aims to improve production process effectiveness in order to sustaining zero defect using Lean Six Sigma method. Define, measure, analyze, improve, and control, known as DMAIC, is used as research approach. The research begun by describing current state map to identify waste that occurs along the value stream. Followed by identifying activities based on three classifications, namely value added, non-value added, and necessary but non-value-added activities. Once such activities known, cost of poor quality and Sigma level is measured. Fish-bone diagram as well as failure mode and effect analysis are used in order to analyze risk priority number. This study found three wastes namely defect, waiting, and inventory as main focus to eliminate then improve effectiveness along production process.